The Labor code of the Philippines : annotations and jurisprudence ; volume one (articles 1 to 155) - Aralar, Reynaldo B (Mandaluyong City, 2005)
The Labor Code of the Philippines, Presidential decree No. 442, as amended aims to distribute wealth to both capital and labor. That way, rather than being dispersed, capital and labor can be brought together
Keywords: Labor laws and legislations -- Philippines